2010
DOI: 10.1002/ibd.21133
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated IL-13Rα2 in intestinal epithelial cells from ulcerative colitis or colorectal cancer initiates MAPK pathway

Abstract: Chronic inflammation in ulcerative colitis (UC) is a sizeable risk factor for colorectal cancer (CRC). Interleukin-13 (IL-13) is elevated in the UC mucosa and may induce dysregulated signaling in neighboring intestinal epithelial cells (IEC) and thus function as a tumorogenic cytokine. Expression of IL-13 receptor chains on IEC obtained from control or chronically inflamed mucosa and colonic tumors was quantified by flow cytometry and immunoblot. IL-13Rα1 and IL-13Rα2 expression is significantly increased on I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…IL-13 is elevated in the ulcerative colitis mucosa and may induce deregulated signaling in neighboring intestinal epithelial cells; therefore, IL-13 may be considered a tumorigenic cytokine. In addition, IL-13Rα2 as a decoy receptor may also participate in modulating the balance and intensity of the signaling pathways initiated in ulcerative colitis and colorectal cancer (20). IL-13-associated pathways are also involved in the development of other tumors.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 is elevated in the ulcerative colitis mucosa and may induce deregulated signaling in neighboring intestinal epithelial cells; therefore, IL-13 may be considered a tumorigenic cytokine. In addition, IL-13Rα2 as a decoy receptor may also participate in modulating the balance and intensity of the signaling pathways initiated in ulcerative colitis and colorectal cancer (20). IL-13-associated pathways are also involved in the development of other tumors.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13Ra2 can be induced by STAT6-dependent as well as STAT6-independent signals (22) and is expressed at elevated levels in fibrotic tissue. Reports have suggested that IL-13Ra2 can transduce STAT6-independent signals that may contribute to fibrosis (23)(24)(25), although these studies relied on ectopic IL-13Ra2 overexpression in cell lines. IL-13Ra2 has a short 17-aa cytoplasmic tail that contains no known canonical signaling motifs, and it has not been shown to form complexes with any other cell surface proteins capable of signaling.…”
mentioning
confidence: 99%
“…Research also shows the elevated level of both IL-13 and its receptors (IL-13Ralpha1 and IL-13Ralpha2) in colon mucosa and colon cancer cells (Mandal and Levine, 2010). IL-13 also appeared to be an activator of the STAT6 pathway (Mandal and Levine, 2010).…”
Section: Discussionmentioning
confidence: 96%